Reputation and International Cooperation : Sovereign Debt across Three Centuries - Tomz, Michael (Book collections on Project MUSE., 2011)
How does cooperation emerge in a condition of international anarchy? Michael Tomz sheds new light on this fundamental question through a study of international debt across three centuries. Tomz develops a reputational theory of cooperation between sovereign governments and foreign investors. He explains how governments acquire reputations in the eyes of investors, and argues that concerns about reputation sustain international lending and repayment. Tomz's theory generates novel predictions about the dynamics of cooperation: how investors treat first-time borrowers, how access to credit evolve.